Phenotypic Variation in Freshwater Murrel, Channa punctatus (Bloch, 1793) from Northern and Eastern Regions of India Using Truss Analysis - Ankur Kashyap; Madhu Awasthi; Mohammad Serajuddin (International Journal of Zoology)
Morphometric variation study was carried out using truss analysis in freshwater murrel, Channa punctatus (Bloch, 1793), to explore different phenotypic stocks of C. punctatus. Significant variation in the morphometric analysis was observed using the truss network and multivariate analysis of the three subpopulations of freshwater murrel, C. punctatus, from the two different regions of India. Principal component analysis accounted for a total variation of 91.95% by the first three principal components. PC 1 represented the variation due to size and PC 2 and PC 3 represented variations due to shape. The 95% confidence ellipses depicted the clear isolation between the samples in scatter graph of PC 1 on PC 2. The combined groups plot (DF 1 on DF 2) based on discriminant function analysis (DFA) also validated the existence of three different subpopulations. In group classification using DFA, 100 percent of all the samples were correctly classified into their original subpopulation. These results support the existence of multiracial composition of C. punctatus across the different geographical isolated sites and, thus, these findings indicate the presence of three different phenotypic stocks of C. punctatus.